Representações implícita e paramétrica de hipersuperfícies algébricas - Silva, Maurício Lourenço Rodrigues da (2019)
The central object of this dissertation are the algebraic hypersurfaces. The main aspect we wish to address is how these hypersurfaces can be represented. More specifically, it is discussed implicit and parametric representations. We will show the advantages and disadvantages of each one of them and also discuss the problem of obtaining a representation from the other.